Congenital Tufting Enteropathy, a Rare Cause of Diarrhea and Malnourishment in Arab Child with Genetic and Histopathology Investigations - Shooq Alkhalifa; Aysha Darwish; Mohamed Awadh; Salman M. Alkhalifa; Abdulla Darwish (Hindawi Limited, 2023)
Congenital tufting enteropathy (CTE), also known as intestinal epithelial dysplasia (IED), is a rare autosomal recessive disorder due to EPCAM gene mutation. It is a rare congenital enteropathy that presents in early infancy as an intractable diarrhea that is independent of breast formula feeding that requires life-long total parental nutrition (TPN) to acquire adequate calories and fluid intake or small bowel transplantation in severe cases. Here, we report a case of intestinal failure due to congenital tufting enteropathy in a 3-year-old girl who presented with loose stools and failure to thrive. This study aims to review the literature about CTE and discuss the clinicopathological aspects and to be able to distinguish it from other causes of congenital diarrheal disorders (CDDs).